2010
DOI: 10.7589/0090-3558-46.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Oil–induced Adrenal Hypertrophy in Ranch Mink (Mustela Vison): Effects of Sex, Fuel Oil Weathering, and Response to Adrenocorticotropic Hormone

Abstract: ABSTRACT:Environmental contamination by petroleum hydrocarbons from anthropogenic sources can be a cause of stress for free-ranging wildlife. The response of wildlife to chemical contaminants requires that the hypothalamic-pituitary-adrenal (HPA) axis be precisely regulated to allow for proper glucocorticoid-mediated adaptive responses. Chronic oral exposure to low concentrations of bunker C fuel oil causes the development of adrenal hypertrophy in male ranch mink (Mustela vison) without increasing serum or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Several studies have shown that PAHs or oil can affect the HPA axis and adrenal gland function. Hypoadrenocorticism has been reported in mink fed either bunker C or artificially weathered fuel oil [ 44 , 45 ]. In these mink, adrenal cortical hypertrophy with vacuolation of corticocytes was detected histologically.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PAHs or oil can affect the HPA axis and adrenal gland function. Hypoadrenocorticism has been reported in mink fed either bunker C or artificially weathered fuel oil [ 44 , 45 ]. In these mink, adrenal cortical hypertrophy with vacuolation of corticocytes was detected histologically.…”
Section: Discussionmentioning
confidence: 99%
“…However, those chronic oral exposures to low concen trations of Bunker C oil did not alter serum or fecal glucocorticoid concentrations. In a second related study, mink were fed artificially weathered fuel oil in their diet for 60 to 62 d, and adrenal hypertrophy was also found at all doses and in both sexes (Mohr et al 2010).…”
Section: Known Toxicological Effects Of Oil Exposure In Turtles and Omentioning
confidence: 97%
“…and mink (e.g. Mohr et al 2008Mohr et al , 2010, as discussed in this section. We compared the estimated exposure in sea turtles to the levels and effects reported in 2 oil dose−response studies in mink (Mohr et al 2008(Mohr et al , 2010.…”
Section: Calculations Of Daily Oil Ingestion Rates In Other Vertebratmentioning
confidence: 99%
See 2 more Smart Citations